2016
DOI: 10.1364/ol.41.003952
|View full text |Cite
|
Sign up to set email alerts
|

Efficient 2122  nm Ho:YAG laser intra-cavity pumped by a narrowband-diode-pumped Tm:YAG laser

Abstract: We first demonstrate an efficient Ho:YAG laser intra-cavity pumped by a narrowband-diode-pumped Tm:YAG laser. The pump wavelength of the laser diode was selected according to the excitation peak which is also one of the absorption peaks of a 3.5 at. % Tm:YAG crystal and was locked by volume Bragg gratings. In the Tm laser experiment, a maximum output power of 11.12 W, corresponding to a slope efficiency of 51.6%, was obtained. In the Ho laser experiment, a maximum output power of 8.03 W at 2122 nm with a slope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…As we know, this is highest diode-to-Ho efficiency reported in Ho:CaF 2 lasers at room temperature. However, compared with the reported intra-cavity pumped Ho laser [12], the slope efficiency is not high, which is mainly caused by the wide pump linewidth. The maximum optical conversion efficiency is 15.8%, which can be increased by a much higher available pump power.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…As we know, this is highest diode-to-Ho efficiency reported in Ho:CaF 2 lasers at room temperature. However, compared with the reported intra-cavity pumped Ho laser [12], the slope efficiency is not high, which is mainly caused by the wide pump linewidth. The maximum optical conversion efficiency is 15.8%, which can be increased by a much higher available pump power.…”
Section: Resultsmentioning
confidence: 58%
“…This poor M 2 value and low efficiency were caused by the serious thermal effects in the Tm:YAG crystal. In order to solve this problem, in 2016 Huang et al employed a narrowband LD to alleviate the thermal effects and improve the laser efficiency, and demonstrated up to 8 W of output power and 38% of slope efficiency in the same laser system [12]. However, due to the short thermal focal length of the Tm:YAG crystal, it is hard to realize a high power under 784.9 nm LD pumping.…”
Section: Introductionmentioning
confidence: 99%
“…Stoneman et al used Tm: YAG laser intracavity-pumped Ho: YAG laser, and realized about 130 mW at 2.09 μm. In 2016, Huang et al reported that an intracavity-pumped Ho: YAG laser by diode-pumped Tm: YAG laser, resulting in 8.03 W at 2122 nm with a slope efficiency of 38%, with the beam quality factors M 2 of 𝑀 𝑥 2 = 2.7 and 𝑀 𝑥 2 = 2.6 [7]. In 2017, Yang et al presented an intracavity-pumped Ho: SSO laser using a Tm: YAP crystal, producing an output power of 1.35W at 2111.4 nm under a pump power of 5.5W, with a slope efficiency of 26.8% [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a strong desire to explore alternative gain mediums for on-chip WGM microlasers. An excellent option is the rare-earth-doped yttrium aluminum garnet (YAG) crystal 35 39 , which is widely recognized as the most popular and successful lasing medium in well-established solid-state bulk lasers. YAG crystal can be doped with various rare-earth elements, allowing for laser emission across a broad range of wavelengths, including ~2.9 μm (Er) 40 , 2 μm (Tm) 41 , 1.6–1.4 μm (Cr) 42 , 1.3 μm (Nd) 43 , 1.06 μm (Nd) 44 , and 1.03 μm (Yb) 45 .…”
Section: Introductionmentioning
confidence: 99%